Consumer Willingness to Pay for Dengue Vaccine (CYD-TDV, Dengvaxia®) in Brazil; Implications for Future Pricing Considerations - Godói, Isabella P.; Santos, André S.; Reis, Edna A.; Lemos, Livia L. P.; Brandão, Cristina M. R.; Alvares, Juliana; Acurcio, Francisco A.; Godman, Brian; Guerra Júnior, Augusto A. (Frontiers in Pharmacology, 2017)
Introduction and objective: Dengue virus is a serious global health problem with an estimated 3.97 billion people at risk for infection worldwide. In December 2015, the first vaccine (CYD-TDV) for dengue prevention was approved in Brazil, developed by Sanofi Pasteur. However, given that the vaccine will potentially be paid via the public health system, information is need regarding consumers’ willingness to pay for the dengue vaccine in the country as well as discussions related to the a possible inclusionorporation of this vaccine into the public health system. This was the objective of this research. Methods: We conducted a cross-sectional study with residents of Greater Belo Horizonte, Minas Gerais, about their willingness to pay for the CYD-TDV vaccine. Results: We interviewed 507 individuals were interviewed. These were mostly female (62.4%) had completed high school (62.17%), were working (74.4%), had private health insurance (64.5%) and did not have dengue (67.4%). Results: The maximum median value of consumers’ willingness to pay for CYD-TDV vaccine is US$33.61 (120.00BRL) for the complete schedule and US$11.20 (40.00BRL) per dose. At the price determined by the Brazil's regulatory chamber of pharmaceutical products market (CMED) for the commercialization of Dengvaxia® for three doses, only 17% of the population expressed willingness to pay for this vaccine. Conclusion: Brazil is currently one of the largestbiggest markets for dengue vaccine and the price established is a key issue for demand. We believe tThe manufacturer should asses the possibility of lower prices to reach a larger audience among the Brazilian population.